2015
DOI: 10.4103/0975-7406.155862
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bleeding during minor oral surgical procedures and extraction in patients on anticoagulant therapy

Abstract: Introduction:The risk of postoperative hemorrhage from oral surgical procedures has been a concern in the treatment of patients who are receiving long-term anticoagulation therapy. A study undertaken in our institution to address questions about the amount and severity of bleeding associated with minor outpatient oral surgery procedures by assessing bleeding in patients who did not alter their anticoagulant regimen.Subjects and Methods:Eighty-three patients receiving long-term anticoagulant therapy visited Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…According to the guidelines developed at the Academic Centre for Dentistry Amsterdam (ACTA), the INR of the patients taking vitamin K antagonists (which is measured within 24–72 h preoperatively) must be ≤3.5 ( Broekema et al, 2014 ). While other studies have reported that an INR < 4 was a safe range prior to dental surgery ( Evans et al, 2002 ; Bacci et al, 2011 ; Karslı et al, 2011 ; Jimson et al, 2015 ). The INR value was less than 4.2 in nine of the included studies in which the OAT patients were being treated with vitamin K antagonists.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…According to the guidelines developed at the Academic Centre for Dentistry Amsterdam (ACTA), the INR of the patients taking vitamin K antagonists (which is measured within 24–72 h preoperatively) must be ≤3.5 ( Broekema et al, 2014 ). While other studies have reported that an INR < 4 was a safe range prior to dental surgery ( Evans et al, 2002 ; Bacci et al, 2011 ; Karslı et al, 2011 ; Jimson et al, 2015 ). The INR value was less than 4.2 in nine of the included studies in which the OAT patients were being treated with vitamin K antagonists.…”
Section: Discussionmentioning
confidence: 82%
“…According to previous reports ( Cannon and Dharmar, 2003 ; Kämmerer et al, 2015 ), minor dental surgery, which is the common procedure in dental health care and routine outpatient treatment, including tooth extractions, dental implant surgery, mucoperiosteal flaps, periodontal surgical procedures, alveoloplasties, limited oral soft tissue surgery, and augmentation procedures (e.g., elevation of the maxillary sinus). Because most of these dental operations can be invasive and hemorrhagic, concern over the safety and efficacy of the OAT and the accompanying bleeding risks related to these invasive dental procedures is unavoidable ( Pototski and Amenabar, 2007 ; Kosyfaki et al, 2011 ; Jimson et al, 2015 ). However, clinical studies evaluating this risk have reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies evaluating the risk of bleeding in patients undergoing minor dental surgery procedures have reported conflicting results. Several studies reported that the postoperative bleeding rate in patients undergoing oral anticoagulant treatment, such as warfarin or coumadin, was not higher than that in patients not undergoing oral anticoagulant treatment [ 18 20 ]. However, some studies have reported more postoperative bleeding in oral anticoagulant treated patients [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…• Continue the same dose of oral anticoagulation with local hemostatic agents • Diminish the dose • Interrupt it altogether a few days before [55] Our review has shown that the first option is the best in most of the dental procedures, with none of the 10 studies recommending the remaining two options since no statistically significant difference in postoperative bleeding existed between most groups continuing and interrupting oral anticoagulation. Other studies have also come to the same conclusion: if INR is acceptable and local hemostatic measures adopted properly during the procedure, then there will be no adverse outcome for continuing oral anticoagulation in dental procedures [56][57][58][59][60], provided according to recent literature normal INR values should be 1.1 or less for normal individuals, and patients on anticoagulant therapy should be within 2.0 to 3.0 to carry out surgical dental procedures. It was recommended that vitamin K antagonists must be continued in all surgical procedures if INR is within the therapeutic range.…”
Section: Anticoagulants and Its Implications In Dentistrymentioning
confidence: 99%